1999
DOI: 10.1016/s0022-2275(20)32090-3
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of the ileal and the hepatic Na+/bile acid cotransporters of the rabbit. II. A reliable 3D QSAR pharmacophore model for the ileal Na+/bile acid cotransporter

Abstract: To design a reliable 3D QSAR model of the intestinal Na ؉ /bile acid cotransporter, we have used a training set of 17 inhibitors of the rabbit ileal Na ؉ /bile acid cotransporter. The IC 50 values of the training set of compounds covered a range of four orders of magnitude for inhibition of [ 3 H]cholyltaurine uptake by CHO cells expressing the rabbit ileal Na ؉ /bile acid cotransporter allowing the generation of a pharmacophore using the CATALYST algorithm. After thorough conformational analysis of each molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Their model identified five pharmacophoric elements: one hydrogen bond acceptor, one hydrogen bond donor, and three hydrophobic interaction points. Interestingly, it was concluded that the 3α-hydroxyl group was not necessary for binding/transport even though iBAs were not examined . More recently, González et al explored the role of the exofacial half of transmembrane domain (TM) 7 of hASBT on BA binding and translocation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their model identified five pharmacophoric elements: one hydrogen bond acceptor, one hydrogen bond donor, and three hydrophobic interaction points. Interestingly, it was concluded that the 3α-hydroxyl group was not necessary for binding/transport even though iBAs were not examined . More recently, González et al explored the role of the exofacial half of transmembrane domain (TM) 7 of hASBT on BA binding and translocation .…”
Section: Discussionmentioning
confidence: 99%
“…However, 3β-hydroxy bile acids were not studied. Subsequently, a QSAR model for ASBT binding was developed by Baringhaus et al using a series of bile acid-like and nonsteroidal hASBT inhibitors . However, their data set did not include native or 3β-hydroxylated BAs, and yet it was concluded that a 3α-hydroxyl group was not necessary for binding/transport of BAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple tools have been developed to study bile acid uptake by ASBT. ASBT function has been studied in vitro with ASBT-expressing (CHO, COS, HEK and MDCK) cells, oocytes, and membrane vesicles derived from those cells (Baringhaus et al, 1999;Zamek-Gliszczynski et al, 2013). The use of wild type or genetically modified animals and in situ perfusion models has also been reported (Baringhaus et al, 1999;Chen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…ASBT function has been studied in vitro with ASBT-expressing (CHO, COS, HEK and MDCK) cells, oocytes, and membrane vesicles derived from those cells (Baringhaus et al, 1999;Zamek-Gliszczynski et al, 2013). The use of wild type or genetically modified animals and in situ perfusion models has also been reported (Baringhaus et al, 1999;Chen et al, 2006). However, these in vitro models differ in many aspects from the conditions in vivo, while animal experiments are costly and a large number of animals is required for statistical evaluation as it allows only one experimental condition per animal.…”
Section: Introductionmentioning
confidence: 99%